A Developmental Hierarchical‐Integrative Perspective on the Emergence of Self‐Regulation: A Replication and Extension. Issue 5 (20th March 2021) - Wu, Qiong; Yan, Jia; Cui, Ming
Abstract : This study replicated and extended the Feldman (2009) study by applying the developmental hierarchical‐integrative model to understand the emergence of self‐regulation. Participants included 360 children (48.6% boys; 62.8% identified as Caucasian and 36.9% African American) and their families, predominantly from a low‐income, rural background. Families completed assessments on child physiological, attention, emotion, and self‐regulation when children were 6‐, 15‐, 24‐, and 36‐month‐old, when caregiver sensitivity was observationally assessed. A path model revealed that child attention regulation at 6 months predicted physiological regulation at 15 months, and child attention regulation at 15 months predicted emotion regulation at 24 months. Attention regulation at 24 months predicted better self‐regulation at 36 months. Notably, caregiver sensitivity moderated several developmental pathways. Findings support a continuous model of early self‐regulation development and the ongoing individual‐environment interplay in early childhood.